Taxonomic revision and morphological delimitation of Oxalis sect. Ripariae (Oxalidaceae) - Nuernberg-Silva, Anelise; Fiaschi, Pedro (Phytotaxa, 2021)
Phylogenetic studies indicate that several infrageneric taxa in Oxalis require taxonomic updates to attain monophyly. In this contribution, we update the morphological delimitation of the South American Oxalis sect. Ripariae and provide a taxonomic revision of the currently accepted species. The sectional delimitation was carried out by comparing micro- and macromorphological features of Oxalis sect. Ripariae, O. sect. Corniculatae, and O. sect. Myriophyllum. These sections share yellow flowers and aerial stems. Glandular hairs and larger seeds with the surface longitudinally crested and with projections are exclusive to Oxalis sect. Ripariae. We accept 11 species in the section, including three previously placed in Oxalis sect. Corniculatae (i.e., O. eriocarpa, O. niederleinii, and O. refracta), but excluding O. serpens and O. subvillosa, which are moved to O. sect. Corniculatae. We also describe a new species (Oxalis lourteiginana), propose a new name and status for O. bifrons subsp. littoralis (now O. pampeana), the synonymization of O. irreperta with O. riparia, six second-step lectotypifications, and one epitypification. For each accepted species we provide a morphological description, illustrations, ecological and taxonomic information, conservation status following IUCN, and a geographic distribution map. Most species occur in southern Brazil, but the section is widespread also in Argentina, Uruguay, and eastern Paraguay. Six species are categorized as threatened and further three as near threatened. Besides, we provide an identification key for the taxa of the section.